Anncaliia algerae Microsporidial Myositis, New South Wales, Australia - Gaurav Sutrave; Adam Maundrell; Caitlin Keighley; Zoe Jennings; Susan Brammah; Min-Xia Wang; Roger Pamphlett; Cameron E. Webb; Damien Stark; Helen Englert; David Gottlieb; Ian Bilmon; et al. (Emerging Infectious Diseases, 2018)
We describe the successful management of Anncaliia algerae microsporidial myositis in a man with graft versus host disease after hemopoietic stem cell transplantation. We also summarize clinical presentation and management approaches and discuss the importance of research into the acquisition of this infection and strategies for prevention.